Pre-service English Teachers’ Pedagogical Competence, Challenges and Strategies to Facilitate Learning - Semi Sukarni; Titi Rokhayati; Tusino (UNIB Press, 2023)
To be able to become a professional teacher, student teachers or pre-service English teachers (PSETs) have to complete the internship teaching program at schools. Here, they learn the teacher competences. This research aims to describe the PSETs’ pedagogical competence reflected in internship program during COVID-19 pandemic; to explain some challenges faced by PSETs in internship program during COVID-19 pandemic and to describe some chosen strategies to overcome the problem. The research employs quantitative and qualitative data collection techniques by involving 32 participants who had just completed their internship program in senior high school and vocational high school. To collect the data, questionnaire and interview were used. The data were analyzed by using descriptive quantitative and qualitative techniques. The quantitative data were analyzed by applying SPSS, while thematic analysis used for the data from interview. The finding suggests that the pedagogical competence of PSETs is “Good” as the mean score of the questionnaire result was 69.60% in the range of 51% to75% mastery the competence. Secondly, there are some challenges faced by PSET in conducting the internship program during the COVID-19 pandemic which are categorized into internal and external factors. Some strategies were applied to overcome the challenges, namely providing appropriate learning media and platform, time management and personal teaching strategies.